Answer:
(a) H0:μ1=μ2; Ha:μ1≠μ2, which is a two-tailed test.
Step-by-step explanation:
We formulate the
H0: μ1=μ2; null hypothesis that the two means are equal and alternate hypothesis that the two mean are not equal.
Ha:μ1≠μ2 Two tailed test
Test statistic used is
t= x1`-x2` / s√n as the variances are equal and sample size is same
T value for 9 degrees of freedom for two tailed test at α = 0.05 is 2.26
P- value for t test for 9 degrees of freedom is 0.125 from the table.
Hence only a is correct .
Hey there!
14 + 3y < 65
SOME people replace “<”, “>”, “≥”, or “≤” as an equal sign (=) to make it easier to solve
14 + 3y < 65
14 + 3y = 65
SUBTRACT by 14 on both of your sides
3y + 14 - 14 = 65 - 14
CANCEL out: 14 - 14 because that gives you 0
KEEP: 65 - 14 because it helps you solve for “y”
**65 - 14 = 51**
NEW EQUATION: 3y = 51
DIVIDE by 3 both of your sides
3y/3 = 51/3
CANCEL out: 3/3 because that gives you 1
KEEP: 51/3 because it gives you the value of “y”
NEW EQUATION: y = 51/3
**51/3 = 17**
Answer: y = 17 ☑️
☑️ OVERALL ANSWER FOR YOU: y < 17 ☑️
NOTE: it’s an OPEN circle SHADED to the LEFT
Good luck on your assignment and enjoy your day!
~LoveYourselfFirst:)
The graph of y=tanx+1 crosses the y-axis at (0,1).
Answer:
15 . Undefined
16. undefined
Step-by-step explanation:
If the pattern continues, so that each term is separated by a distance of 3, then the sequence is given by the recursive rule
![\begin{cases}a_1=1\\a_n=a_{n-1}+3&\text{for }n>1\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_1%3D1%5C%5Ca_n%3Da_%7Bn-1%7D%2B3%26%5Ctext%7Bfor%20%7Dn%3E1%5Cend%7Bcases%7D)
From this definition, we can write
in terms of
:
![a_2=a_1+3](https://tex.z-dn.net/?f=a_2%3Da_1%2B3)
![a_3=a_2+3=(a_1+3)+3=a_1+2\cdot3](https://tex.z-dn.net/?f=a_3%3Da_2%2B3%3D%28a_1%2B3%29%2B3%3Da_1%2B2%5Ccdot3)
![a_4=a_3+3=(a_1+2\cdot3)+3=a_1+3\cdot3](https://tex.z-dn.net/?f=a_4%3Da_3%2B3%3D%28a_1%2B2%5Ccdot3%29%2B3%3Da_1%2B3%5Ccdot3)
![a_5=a_4+3=(a_1+3\cdot3)+3=a_1+4\cdot3](https://tex.z-dn.net/?f=a_5%3Da_4%2B3%3D%28a_1%2B3%5Ccdot3%29%2B3%3Da_1%2B4%5Ccdot3)
and so on, up to
![a_n=a_1+(n-1)\cdot3](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n-1%29%5Ccdot3)
(notice how the subscript on <em>a</em> and coefficient on 3 add up to <em>n</em>)
or
![a_n=1+3(n-1)=3n-2](https://tex.z-dn.net/?f=a_n%3D1%2B3%28n-1%29%3D3n-2)